Foundational processes and growth - Wing Wah Tham; Salomé Baslandze; Elvira Sojli; Leo Liu (Federal Reserve Bank of Atlanta, 2025)
This paper studies the interaction between process and product innovations and their distinct role in firm growth dynamics. We differentiate empirically and theoretically two types of process innovations: foundational processes that advance production technology and cost-reducing processes that enhance existing production efficiency. We develop an innovation model of product varieties with quality heterogeneity to illustrate how these innovations affect firm growth differently and highlight how process innovation induces product innovation. By analyzing millions of patent texts from 1900 to 2020, we classify innovations into product, cost-reducing process, and foundational process innovations. We find that foundational processes lead to sustained firm growth, especially through their effect on subsequent product creation. R&D-intensive firms focused on "deep-tech" innovations have an advantage in creating foundational processes, resulting in superior product quality. Using patents linked to FDA-approved drugs, we show that firms with a comparative advantage in creating foundational processes, due to greater knowledge and technological stock, tend to produce higher-value products.
Keywords: O3; O4; 330; foundational process innovation; process innovation; product innovation; process-driven products; firm growth; technological possibility frontier